The Minimal - Sized Ships with a Small Water-Plane Area - Dubrovsky, Victor A. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2013)
In theory, a small water-plane area results in a larger than usual immersion of the main displacement volume of a ship’s hull(s).Although practical realization of this theory typically involves an unusually large draft, small vessels tend to have small enough drafts. This contradiction demonstrates the problem associated with a minimal-sized ship with a small water-plane area (SWA ships). Here restrictions in terms of possible displacement and dimensions are described, with the range of minimal displacement and dimensions of an SWA ship estimated and alternative options outlined on the base of [1], [2], [3], [4]. (A SWA hull consists of an under-water gondola as the main displacement volume,together with one or more struts connecting the gondola to the above-water platform. Evidently, the struts intersect the watersurface at design draft.).